Efficacy of liraglutide in patients with metabolic-associated steatotic liver disease in type 2 diabetes mellitus - Yu.M. Stepanov; O.V. Zinych; I.A. Klenina; K.O. Shyshkan-Shyshova; N.M. Kushnarоva (Gastroenterologìa)
Background. The increasing incidence of metabolism-associated steatotic liver disease (MASLD) and type 2 diabetes prompts physicians to improve strategies for the diagnosis, prevention, and treatment of these metabolic conditions. Objective: to investigate the effects of glucagon-like peptide-1 receptor agonist (arGLP-1) on the severity of metabolic disorders in patients with MASLD and type 2 diabetes mellitus in the dynamics of treatment. Materials and methods. The study included 30 patients aged (56.5 ± 7.8) years with MASLD and type 2 diabetes mellitus. They were prescribed liraglutide, a arGLP-1, with gradual titration to the maximum dose. To assess body composition, body composition analyzers TANITA BC-545N (Japan) were used. Serum levels of glucose, glycosylated hemoglobin (HbA1c), parameters of lipid and carbohydrate metabolism were determined. The atherogenic index was calculated according to the formula of W.T. Friedewald, the TyG, TyG-BMI, TyG-WC indices were calculated based on the obtained bioimpedance analysis data, as well as lipid and carbohydrate metabolism indicators. Statistical processing of the study results was carried out by methods of variation statistics using the software package StatSoft Statistica 10.0. Results. After treatment with arGLP-1, a significant decrease in serum glucose to physiological norm was observed in 26.7 % of patients, and a reduction in HbA1c levels — in 66.7 %. The therapy led to a reduction in body mass index in 28 (93.3 %) of 30 patients, in body fat percentage — in 25 (83.3 %), and the number of cases of visceral obesity decreased to 17 (56.7 %). After the use of arGLP-1, a positive trend was observed in the form of a 1.3-fold decrease in serum triglyceride levels to (1.64 ± 0.20) mmol/L versus (2.12 ± 0.25) mmol/L before treatment. Serum cholesterol, which was elevated in 11 patients, reduced in 6 cases after therapy. The use of liraglutide led to a reduction in the TyG, TyG-BMI, TyG-WC indices. Conclusions. In patients with MASLD and type 2 diabetes, treatment with liraglutide for 6 months contributed to a decrease in the amount of fat in body composition and a positive dynamics of carbohydrate and lipid metabolism. The determination of the TyG index is a useful indicator for assessing insulin resistance, and the TyG-BMI and TyG-WC indices are recommended to be used as an affordable alternative for monitoring the effectiveness of treatment.